Perforation Modes of Metal Plates Struck by a Blunt Rigid Projectile - XIAOWEI, Chen; GUANJUN, Liang (Engineering Transactions, 2012)
The present paper analyzes the possible modes of shear plugging and adiabatic shear plugging in the perforation of metal plates struck by a blunt rigid projectile. The modified ballistic limit and residual velocity under the condition of adiabatic shear plugging are further formulated. Further experimental analyses are conducted on the perforations of Weldox E steel plates in order to discuss the effects of plate thickness and material strength/hardness on the terminal ballistic performance. More experimental evidence confirms the jump of residual velocity at the ballistic limit induced by the structural response of the plate. With increasing the thickness of plate and the material strength, failure modes of the plate may transform from shear plugging to adiabatic shear plugging.